A SWOT ANALYSIS OF THE INNOVATION BOX AS A TAX INSTRUMENT TO SUPPORT INNOVATION BY ENTERPRISES IN POLAND - Katarzyna Łukaszewska; Edyta Małecka-Ziembińska (Polityki Europejskie, Finanse i Marketing)
The Innovation Box – a tax relief introduced in Poland in 2019, serves as a complementary element of fiscal support and the final link in the chain of innovation support. This preference isnot applied at the stage of creating new solutions (as was the case with the tax relief for purchasing new technologies and has been the case with tax relief for research and developmentactivity since 2016), but at the stage of their commercialisation. It may, thus, contribute to a greater interest and scale of application of the relief for research and development activity. Theaim of this article is to present the essence of the Innovation Box, as well as to conduct a SWOT analysis of this tax relief as an instrument of support for innovation by enterprises. A SWOTanalysis has corroborated the remarks – previously made by industry practitioners – concerning the ambiguous and complicated mechanism of the Innovation Box. However, along with theconsolidation of the practice of applying this tax relief, interest in it may increase, which in turn might be conducive to Polish enterprises.